1989
DOI: 10.1164/ajrccm/140.6.1595
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alveolar Macrophages in the Neutrophil-dependent Defense System againstPseudomonas aeruginosaInfection in the Lower Respiratory Tract: Amplifying Effect of Muramyl Dipeptide Analog

Abstract: Alveolar macrophages are thought to be important in immune or inflammatory reactions. We investigated the role of alveolar macrophages in defense against Pseudomonas aeruginosa infection in the lower respiratory tract. Intratracheal inoculation of formalin-inactivated P. aeruginosa (1 x 10(8)-1 x 10(10) organisms) into normal rats resulted in increase in the number of neutrophils in the bronchoalveolar lavage (BAL) fluid obtained 24 h later. The phagocytic activity of neutrophils for P. aeruginosa was higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…Previous findings also indicate that lung epithelial cells may play a key role in the production of proinflammatory cytokines (25,26). Consistent with previous studies, we also found that activation of two signaling proteins (JNK and NF-B) was blunted in both TPRC1-silenced epithelial cells and TRPC1 Ϫ/Ϫ mice (38,39). Critically, we reveal a new mechanism by identifying that Ca 2ϩ entry via TRPC1 is essential for the activation.…”
Section: Discussionsupporting
confidence: 92%
“…Previous findings also indicate that lung epithelial cells may play a key role in the production of proinflammatory cytokines (25,26). Consistent with previous studies, we also found that activation of two signaling proteins (JNK and NF-B) was blunted in both TPRC1-silenced epithelial cells and TRPC1 Ϫ/Ϫ mice (38,39). Critically, we reveal a new mechanism by identifying that Ca 2ϩ entry via TRPC1 is essential for the activation.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the lungs of cav1 KO mice exhibit increases in proinflammatory cytokines, but a similar increase was not found in the BAL fluid of these mice. Thus, lung epithelial cells might also contribute to the production of cytokines (41,58,59), whereas macrophages and neutrophils are traditionally regarded as the main players in inflammatory responses (60). To further explore the dysregulation of inflammatory response in KO mice, modifications of the cell signaling pathway in the lungs were examined.…”
Section: Discussionmentioning
confidence: 99%
“…In the uninfected or untreated lung, PMNs comprise a small proportion of cells in the lower respiratory tract and macrophages constitute 85 to 98% of cells (15,26,29). However, the number of PMNs increases in lungs challenged with P. aeruginosa by intratracheal inoculation (19).…”
Section: Discussionmentioning
confidence: 99%